Growth kinetics of Myceliophthora thermophila M.7·7 in solid-state cultivation - dos Santos Gomes, A. C. [UNESP]; Casciatori, F. P.; Gomes, E. [UNESP]; da Costa Carreira Nunes, C. [UNESP]; Moretti, M. M.S. [UNESP]; Thoméo, J. C. [UNESP] (Oxford University Press (OUP), 2020)
Aims: This work aimed to estimate the growth of Myceliophthora thermophila M.7·7 in solid-state cultivation (SSC) through quantification of N-acetyl-d-glucosamine (NAG) and enzyme activity. Methods and Results: The fungus was cultivated in sugarcane bagasse and wheat bran. A consistent statistical analysis was done to assess the reliability of experimental data. Logistic model equation was fitted to experimental data and growth parameters were estimated. The results showed strong influence of the sample size on NAG and a minimum recommended sample size was identified. Scanning electron microscopy (SEM) was used to identify the strategy of substrate colonization. Wheat bran was attacked firstly, while sugarcane bagasse was consumed after wheat bran depletion. The biomass growth was poorly estimated by secretion kinetics of α-amylase, endoglucanase, protease and xylanase, but enzyme kinetics were important for understanding substrate colonization. Conclusions: In conclusion, the NAG concentration was strongly affected by the sample size and sampling procedure. The strategy of fungal colonization on the substrates was well characterized through SEM analysis. The colonization strategy has direct influence on the kinetic parameters of the logistic model. Myceliophthora thermophila has a well-defined dynamic of enzyme secretion to degrade the substrate, although the kinetics of enzyme secretion has shown not adequate to characterize the kinetics of fungal growth. Significance and Impact of the Study: The paper provides reliable growth kinetic parameters in the SSC of the cellulase producer fungus M. thermophila M.7·7, as well as a robust analysis on three indirect methods (NAG, enzymes and SEM) for estimation of fungal development.
Keywords: enzymes; growth kinetics; logistic model; N-acetylglucosamine; solid-state cultivation